Optimizing New Product Development in The Hijab Industry: A House of Risk Analysis on Marketing and Design Process - Wijaya, Muhammad Agusta; Handayani, Dwi; Basuki, Demas Emirbuwono; Mukarim, Rifki Nurul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
XYZ Company, a Micro, Small, and Medium Enterprise (MSME) based in Yogyakarta, specializes in producing hijabs but faces challenges in maintaining customer interest due to a misalignment between product designs and consumer preferences. To address this, the company actively engages in new product development (NPD), focusing on trend analysis and model innovation to cater to customer needs better. An essential part of minimizing risks during the NPD process involves evaluating and identifying potential pitfalls, particularly in marketing and design. This study employs the Hazard and Operability Review (HOR) method to assess risks systematically. Initial findings from HOR phase 1 reveal that inadequate competitor information (A3) leads to significant risks in competitor product identification (E3), contributing approximately 70.34% to the total Aggregate Risk Priority (ARP). Subsequently, in HOR phase 2, XYZ Company prioritizes ten mitigation actions, with conducting a comparative study of competitors' products (PA1) being the most critical, reflected by an ETDk value of 540. Keywords: House of Risk (HOR), Hijab Fashion, Hijab Industry, New Product Development (NPD)